2004
DOI: 10.1080/09540120412331269594
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to employment among persons living with HIV/AIDS

Abstract: This study examined factors associated with contemplating returning to work among unemployed persons living with HIV/AIDS (PLHA) in a large urban city in the United States. A mailed, self-administered survey gathered information from 757 unemployed PLHA. Chi-square and logistic regression analyses were used to determine associations between contemplating returning to work and sociodemographic characteristics, health factors and perceived barriers to employment. We found that most unemployed PLHA (74%) were thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 26 publications
4
83
0
3
Order By: Relevance
“…A study conducted by Brooks, et al (2004), reported that 66% of unemployed PLWHA in the United States indicated that workplace discrimination along with the loss of health insurance and disability income benefits were significant barriers to returning to work (Brooks, et al 2004). This study clearly indicates that work place discrimination exists; 12% of participants indicated that they would change jobs if someone they work with becomes positive for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Brooks, et al (2004), reported that 66% of unemployed PLWHA in the United States indicated that workplace discrimination along with the loss of health insurance and disability income benefits were significant barriers to returning to work (Brooks, et al 2004). This study clearly indicates that work place discrimination exists; 12% of participants indicated that they would change jobs if someone they work with becomes positive for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Ello provoca que sea la discriminaci贸n social un tema de inter茅s comunitario. Los estereotipos asociados tradicionalmente al VIH contin煤an jugando un importante papel en la justificaci贸n, desarrollo y mantenimiento de la estigmatizaci贸n hacia las personas seropositivas (Brooks, Mart铆n, Ortiz y Veniegas, 2004;Dijker, Kok y Koomen, 1996). Esta estigmatizaci贸n se da tanto en lo f铆sico y social como en lo verbal e institucional, siendo especialmente dram谩tica esta 煤ltima, lo que conlleva dificultades de acceso a la vivienda, la educaci贸n o el mundo del trabajo.…”
Section: Discusi贸n Y Reflexiones Finalesunclassified
“…Three studies noted that, for people currently not working, fear of being stigmatized by colleagues was a major barrier to obtaining employment [25,29,36]. The other study described the perception of many participants, that employers are not HIV sensitive and that the Americans with Disabilities Act would not protect them from discrimination [37].…”
Section: Fear Of Stigmamentioning
confidence: 99%
“…Three studies reported that disclosure is sometimes necessary because of a change in health status, such as progression of the illness which may lead to absences [22,24,29].…”
Section: Changing Health Statusmentioning
confidence: 99%
See 1 more Smart Citation